Psychological Characteristics Affecting the Adoption of Agricultural Technologies - Seema Naberia , U.S. Gautam & Aroop Kumar Gupta, (Indian Journal of Extension Education, 2015)
A study was conducted to find out the influence of psychological characteristics in adoption of low cost technologies byfarmwomen having small and marginal land holding. The study was conducted under Madhya Pradesh Women inAgriculture Programme in Katni district of Madhya Pradesh. Data were collected through pretested structured interviewschedule and the relationship between the dependent variables and adoption was studied using correlation analysis. Thestudy leads to the conclusion that both the categories of beneficiaries had different level of adoption. The psychologicalattributes of the beneficiaries like economic motivation, risk orientation, scientific orientation and knowledge were foundto be positively and significantly correlated with the adoption of low cost technologies taken under MAPWAprogramme.